PENERAPAN SEQUENTIAL SEARCH UNTUK PENGELOLAAN DATA BARANG - Kartiko Ardi Widodo; Suryo Adi Wibowo; Nurlaily Vendyansyah (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
The industrial technology 4.0 is very meaningful in the manufacturing industry, especially in managing stock of goods as one example. Managing data on goods in a company is a crusial problem and must be handled carefully. Because this will affect the survival cycle of the company. In the field of informatics, this problem can be solved with a theory in the field of informatics, especially by searching methods. In this study, the authors applied one of the searching methods, namely sequential search which was then implemented for the process of searching for goods data at the PD. XYZ.This a company engaged in automotive services and goods. The sequential search method is implemented in the EditText component to search for item data. Tests are carried out to determine the performance of the sequential search method, by conducting an experiment by providing input to the Edit Text component. The sequential search method can perform a search process for words (phrases) in the database with a total of 800 data samples, and the result is that the average search speed is 0.2 seconds.